Composite structural batteries with Co3O4/CNT modified carbon fibers as anode: Computational insights on the interfacial behavior. (5th January 2021) - Hu, Zihan; Fu, Yu; Hong, Zhiguo; Huang, Yao; Guo, Weihua; Yang, Ruiheng; Xu, Jun; Zhou, Limin; Yin, Sha
Abstract: Interface is vital for high-performance composites. We report energy-storage structural composites with Co3 O4 /CNT modified carbon fiber as anodes, aiming at enhancing their electrochemical and interfacial stability simultaneously. The interfacial failure is readily to occur at fiber/matrix interface as volume of Co3 O4 active particles expands during charging, and thus carbon nanotubes (CNTs) are incorporated surrounding active particles. The interfacial failure mechanism is investigated using a cohesive zone model (CZM). Effects of CNT addition, CNT density, particle geometry and patterns, and failure criterion parameters of polymer electrolyte on the interfacial behavior are all discussed. After CNT addition, failure will initiate at CNT/matrix interface instead of CF/matrix interface for anode without CNT. Also, particle patterns with nonuniform density that can decrease stress near CF interface and enable deformation outward (or absorb deformation) will ensure excellent interfacial performance. Polygonal particles infinitely close to a circular sphere shape possessing small gap/voids between CNTs will be ideal. The findings in this work will provide novel pathways for the design and fabrication of composite structural batteries with high interfacial stability. Graphical abstract: Image 1 Highlights: Structural battery with CNT/Co3 O4 modified carbon fibers (CFs) is proposed. Cohesive zone model is employed to investigate the interfacial failure behavior. Failure initiates at CNT/matrix interface instead of CF/matrix after CNT addition. Particle patterns and electrolyte properties are vital for interfacial stability.